2004
DOI: 10.1080/16501970310015218
|View full text |Cite
|
Sign up to set email alerts
|

Tender or not tender: test-retest repeatability of pressure pain thresholds in the trapezius and deltoid muscles of healthy women

Abstract: Repeated measurements show stable intra-individual values. The method can be recommended when used by trained and experienced examiners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 25 publications
(49 reference statements)
9
104
1
Order By: Relevance
“…Klaesner et al also developed a handheld portable indention system but with very high interrater and intrarater reliability (ICC values = 0.99) [4]. The ICC values on PPT (Table 3) [47], when a pressure algometer was used. Precise control of the indentation speed and indentation direction may have contributed to the high measurement reliability of PPT.…”
Section: Indentation Of Foot Tissuementioning
confidence: 99%
“…Klaesner et al also developed a handheld portable indention system but with very high interrater and intrarater reliability (ICC values = 0.99) [4]. The ICC values on PPT (Table 3) [47], when a pressure algometer was used. Precise control of the indentation speed and indentation direction may have contributed to the high measurement reliability of PPT.…”
Section: Indentation Of Foot Tissuementioning
confidence: 99%
“…29,30 The pressure of compression was increased gradually at a speed of ∼1 kg/s. The participant was asked to say 'yes' as soon as pain or discomfort occurred and at this moment the compression was stopped.…”
Section: Pressure Pain Thresholdmentioning
confidence: 99%
“…For the purpose of this study, the examiner underwent a training session in the days prior to testing which consisted of multiple practice trials on several willing participants' spines. The high correlation values may be a reflection of this training, however the training procedure was minimal and may allow the device to be used as a single pre-test and post-test measure 15 and therefore appropriate for routine use in clinical practice. The use of the device could be as outcome measure for spinal complaints to quantify the subjective changes in pain reported by patient.…”
Section: Discussionmentioning
confidence: 99%
“…The spinous processes of C6, T6 and L4 were selected for assessment as they have been used in a previous study, 1 and therefore discussion of the results of the present in relation to this previous study is possible. The PPT for each segment was measured three times in order to obtain an average PPT value, as studies 6 have shown that the mean of more than one trial is the most reliable estimate of the PPT, 11 in particular if the first trial is excluded, 6,15 The algometer was positioned perpendicular to the body surface at the specified spinous processes and the pressure was increased at a rate of 40 kPa/sec. 9,15 Previous research has indicated that a constant rate of pressure application increases reliability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation